Desain Sistem Informasi untuk Pengelolaan Produksi Sarang Burung Walet Berbasis ISO 22000:2018 - Anang Kukuh Adisusilo; Emmy Wahyuningtyas; Siti Gusti Ningrum; Linda Wijayanti; Melisa Mulyadi (Walisongo Journal of Information Technology, 2023)
The swallow's nest industry is an important sector in the food industry, especially in Asia, because the products are used in various food and beverage products. However, the sustainability and success of this industry depend on food safety and the quality of the products produced. In the context of globalization and increasing competition, it is important for bird's nest producers to ensure that their products meet international food safety standards. One standard that provides comprehensive guidelines for ensuring food safety from production to consumption is ISO 22000:2018. Efficient implementation of ISO 22000:2018 still faces difficulties such as tracking production processes, managing production processes, ensuring compliance with regulations, and responding quickly to changes in market demand. These obstacles can cause production failures and even export failures because standards are not met. By using a computer-based system, in this case, the use of an information system, especially for managing the swallow's nest production process, you can manage it more efficiently and effectively because all flows are recorded so that they can also be tracked, stored, and the data is more valid. After conducting the needs analysis, the research flow was designed to design a system starting from user interfaces, data flow design using DFD, and database design using ERD.The research results show that swallow's nest producers can improve the quality of their products to meet applicable food safety regulations by producing up to 150 ISO reporting documents to accelerate the fulfilment of consumer needs and have the impact of expanding market share.